Carbon Monoliths: Ultra‐High Pyridinic N‐Doped Porous Carbon Monolith Enabling High‐Capacity K‐Ion Battery Anodes for Both Half‐Cell and Full‐Cell Applications (Adv. Mater. 35/2017). Issue 35 (September 2017) - Xie, Yihao; Chen, Yu; Liu, Lei; Tao, Peng; Fan, Mouping; Xu, Na; Shen, Xiaowei; Yan, Chenglin
Abstract : Owing to the lower cost and easy accessibility of potassium, potassium‐ion batteries are considered as potential substitutes for lithium‐ion batteries. A porous carbon monolith with ultrahigh pyridinic N content is successfully synthesized by Yu Chen, Chenglin Yan, and co‐workers in article1702268, which exhibits excellent electrochemical performance, especially in terms of reversible capacity, for both K + half‐cells and full‐cells.